Naubatkhana and deepsthambh at the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
Diverse architectural elements are incorporated within a compact forecourt at the Vyankatesh Balaji Temple. The entrance gate doubles as a naubatkhana (drum house); a flight of steps leads to a platform where musicians played the nagara and shehnai. Next to the gateway are shrines dedicated to Garuda and Ganesha, separated by a deepastambha.